Penerapan Kepemimpinan Etis Dalam Mewujudkan Good Governance Pada Organisasi Modern - Septerina Putri Zebua (CV. SINAR HOWUHOWU, 2026)
Ethical leadership has become one of the essential elements in supporting the implementation of good governance within modern organizations. Rapid organizational development and increasingly complex managerial challenges require leaders who are not only competent in decision-making but also capable of maintaining ethical values, integrity, accountability, and transparency. This study aims to analyze the role of ethical leadership in creating effective and sustainable good governance. The research method used is a literature review by examining various national and international scientific journals, books, and academic publications related to ethical leadership and organizational governance. The results indicate that ethical leadership significantly influences organizational culture, employee trust, work discipline, accountability, and transparency in decision-making processes. Ethical leaders are able to become role models in implementing organizational values consistently and professionally. Furthermore, ethical leadership contributes positively to increasing organizational effectiveness and strengthening governance systems. Therefore, the implementation of ethical leadership is considered an important foundation in realizing good governance in modern organizations.